The study of the properties of concrete containing waste powder as a fine aggregate - Dobiszewska, Magdalena; Wrzecion, Krzysztof (International Conference “Environmental Engineering”, 2017)
Concrete production consumes much energy and large amounts of natural resources. It causes environmental, energy and economic losses. Cement industry contributes to production for about 7% of all CO2 generated in the world. Every ton of cement production releases nearly one ton of CO2 to atmosphere. Thus the concrete and cement industry changes the environment appearance and affects it to a great extent. On the other hand, there is an increase in demand and decrease in natural sources of concrete constituents, like sand. The use of rock dust as the replacement for natural sand will solve the problem of dust disposal. The present study shows the results of the research concerning the modification of concrete with waste dust. It is the waste from the preparation of aggregate used in asphalt mixture production. Concrete modification consists in that the powder waste is added to concrete as partial replacement of fine aggregate. Previous studies have shown that analysed waste has a beneficial effect on compressive strength, flexural strength as well as freeze resistance. The use of mineral powder as the partial substitution of fine aggregate allows for the effective management of industrial waste and improves some properties of concrete.